SISTEM INFORMASI ADMINISRASI DAN DATA REKAM MEDIS PASIEN PADA KLINIK SOLEH ALI BERBASIS WEB - Aluisius Dwiki Adhi Putra; Arif Hidayatulloh; Andhika Setyawardhana; Tri Ika Jaya Kusumawati (Journal Information System Development (ISD), 2020)
Abstract-- Soleh Ali Clinic is an institution engaged in the field of public health. In the Soleh Ali Clinic in patient data collection, drugs, prescriptions, and reports still use the manual way still using paper as a storage medium that can save time in searching patient data related to medical records as well as in patient reports or reports in the clinic. Information System Development Method created by us using SDLC with tools such as DFD in accordance with the database design proposed by ERD. While the data collection techniques used interview, observation and literature study methods. The implementation program carried out on this information system uses the PHP programming language with the CodeIgniter framework and also uses the MySql database. The information system created can overcome the problems that exist in the Soleh Ali Clinic in storing patient data, medical record data and also drug data making the process of public health services can be done quickly, efficiently and also avoid problems that are done manually. Keywords: Information System, Php, Sholeh Ali, Web, Administration